Pemantauan Pasien Dengan Diagnosa Gagal Ginjal Kronik Di RSUD Sumber Rejo Bojonegoro - Rinza Rahmawati Samsudin; Rahma Widyastuti; Nur Vita Purwaningsih (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2021)
The kidneys are important organs that function to maintain blood composition by preventing the accumulation of waste and controlling the balance of fluids in the body. Chronic Kidney Disease (CKD) has become a major health problem of Indonesian people. Creatinine examination become one of the choices to identify the index of the kidney severity. The purpose of this study was to determine the description of creatinine levels of patients diagnosed with Chronic Kidney Disease (CKD). This research used descriptive method. The population of this study was patients with the diagnosis of Chronic Kidney Disease (CKD) who conduct the examination of creatinine levels in the installation of Pathology ClinicLaboratory which amounted to 100 patients during April to May. This research used the secondary data obtained and collected from the LIS (Laboratory Information System) and the medical record. The result of this study showed tht 73% of 100 patients diagnosed with Chronic Kidney Disease (CKD) are not normal, and the 27% data of creatinine levels is normal. Presentations of male patient who experienced levels of creatinine was high, namely 37 patients compared female. The incidence of patients with Chronic Kidney Disease (CKD) the highest range of productive age of 20-64 years was 50 patients (68%). The results of the research of the average content on patients diagnosed with Chronic Kidney Disease (CKD) obtained the creatinine level average of 4.01 mg/dl.   Keywords: Chronic Kidney Disease (CKD), Creatinine